KOMUNIKASI KELUARGA DALAM MEMBANGUN KEPERCAYAAN ORANG TUA TERHADAP ANAK: (Studi Deskriptif pada Hubungan Keluarga di Bandung) - Indah Sri Gustiani; Mega Rahma Adelia; Syaira Septianisa Ramdhan; Humada Nanda Maspupah; Rama Wijaya Abdul Rozak (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research employs qualitative methods, with various techniques for gathering data include observation, documentation, and interviews. The research conducted is a descriptive study, which describes the interaction among children and parents. The subjects of the study are parents of children. The data collection methods include observation, interviews, and document analysis.. The data validation technique employs data collection and analysis from various sources through direct interviews. The purpose is to examine patterns of parental interaction influence of children self confidence.. Interaction plays a role in a life, as the initial and direct interaction experienced by a child with their parents. Therefore, the significance of communication. should be instilled early on, as it is as crucial as building a child's self-confidence. Based on the research conducted with 3 samples, it was found that parents who use democratic patterns, parents who apply permissive patterns, and parents who also apply authoritarian patterns. The trust established through effective communication allows children to feel safe, valued, and supported in their development. Active listening, honesty, and positive non-verbal communication are key elements that form the foundation of the trust bond between parents and children.